2000
DOI: 10.1093/tropej/46.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Brief report. Hepatic dysfunction in childhood dengue infection

Abstract: Hepatic functions of 61 children, diagnosed to have dengue infection (DI), aged 2 months to 12 years comprising 37 cases of dengue fever (DF), 16 with dengue hemorrhagic fever (DHF), and eight with dengue shock syndrome (DSS) were prospectively studied during the acute attack. Hepatomegaly (74 per cent), epistaxis (26 per cent), jaundice (25 per cent), and petechial rashes (18 per cent) were the common clinical manifestations of DI. On admission, levels of serum aspartate transaminase (AST), serum alanine tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
117
1
7

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(139 citation statements)
references
References 0 publications
14
117
1
7
Order By: Relevance
“…The reduction in serum globulin is an important factor in fluid loss into the third space, which is indicative of severity in dengue due to a reduction in the gradient of intra-and extravascular pressure. These findings have been confirmed by other authors in cases of hepatitis in dengue shock syndrome [10,12]. Therefore, AST, ALT and globulin are valuable parameters for the evaluation of the severity of the infection.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The reduction in serum globulin is an important factor in fluid loss into the third space, which is indicative of severity in dengue due to a reduction in the gradient of intra-and extravascular pressure. These findings have been confirmed by other authors in cases of hepatitis in dengue shock syndrome [10,12]. Therefore, AST, ALT and globulin are valuable parameters for the evaluation of the severity of the infection.…”
Section: Discussionsupporting
confidence: 75%
“…The extent to which the liver is affected by DENV ranges from mild lesions to fulminant hepatitis [5,[9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the liver tissue showed extensive cell cytopathic effects as vacuolization and intracellular edema; the architecture of the hepatic lobules was partially destroyed; sinusoids were partially collapsed; only a minimal and diffusely distributed mononuclear inflammatory infiltrate was visible; blood vessels were dilated; In humans, DENV has been frequently isolated from the liver, and the antigens have been detected in Kupffer cells and hepatocytes (Rosen et al 1989, Bhamarapravati 1997, Couverland et al 1999. Liver function tests showed high levels of serum aspartate transaminase (AST) and serum alanine transaminase (ALT) activity, indicating hepatic injury (Kuo et al 1992, Nguyen et al 1997, Mohan et al 2000. Histologically the most common features in the liver were small foci of necrosis and microvesicular steatosis (Bhamarapravati et al 1967, Burke 1968, Fresh et al 1969.…”
mentioning
confidence: 99%
“…Liver function tests showed high levels of serum aspartate transaminase (AST) and serum alanine transaminase (ALT) activity, indicating hepatic injury (Kuo et al 1992, Nguyen et al 1997, Mohan et al 2000. Histologically the most common features in the liver were small foci of necrosis and microvesicular steatosis (Bhamarapravati et al 1967, Burke 1968, Fresh et al 1969.…”
mentioning
confidence: 99%
“…Cases with positive IgM for a single sample would be probable dengue cases since the finding can persist for up to 90 days. Despite this, probable and confirmed cases have been analyzed in conjunction in some studies 14,26,27 and the Health Ministry defines confirmed cases of dengue as those in which IgM is positive in association with indicative clinical and epidemiological status. 3 According to that definition, around 50% of the children with acute nonspecific febrile diseases had dengue.…”
Section: Discussionmentioning
confidence: 99%